(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Raw water is natural water found in lakes, rivers, streams, and underground sources before any treatment or purification processes. It typically contains various impurities, such as suspended solids, organic matter, pathogens, and dissolved minerals, which need to be removed to make it safe for consumption. Aluminum Sulfate and Poly Aluminum Chloride (PAC) are two commonly used chemicals in the treatment of raw water to remove impurities and make it suitable for drinking, industrial, or agricultural purposes. These chemicals play crucial roles in the purification process by aiding in the coagulation and flocculation of contaminants, which facilitates their removal through filtration. Study on raw water treatment using Aluminum Sulphate and Poly Aluminum Chloride (PAC) coagulants was carried out at Talang Jawa IPA PDAM Lematang Enim of Muara Enim District by taking raw water samples from Talang Jawa Intake and Pelita Sari Intake. This study aimed to find out the right type and dose of coagulant in the raw water treatment process. he test parameters were turbidity and pH values. The research was conducted using a jar test to determine the dose of coagulant. The results showed the use of solid PAC was more effective for both intakes. The optimum coagulant dose is 20 ppm PAC in the raw water of Talang Jawa intake and Pelita Sari intake with turbidity of 2.62 NTU and 4.15 NTU and pH of 7.8 and 7.6.